Clinico-pathological profiles of sub-fertility in Zebu Cows - Pariza, KF; Bari, ASM; Bari, FY; Alam, MGS; Noor, M (Bangladesh Veterinarian, 2010)
Blood samples from cows with reproductive problems (anoestrus, repeat breeder, uterine infection) were collected for haematological, biochemical and humoral immune response analyses. The erythrocyte sedimentation rate (ESR) was higher and haemoglobin (Hb) lowers in subfertile cows than innormal cycling cows. The packed cell volume (PCV) was lower in anoestrus and repeat breeding cows than in control. Total erythrocyte count (TEC) was not significantly different, whereas total leukocyte count (TLC) significantly higher (p<0.01) in anoestrus and repeat breeder cows. The bilirubin concentration was significantly higher (p<0.005) in anoestrus and uterine infected cows compared with control. The mean serum IgG was lower in all subfertile cows than control. It is suggested that there is no specific clinico-pathological marker for reproductive disorders in cows. DOI: 10.3329/bvet.v26i1.4624 Bangl. vet. 2009. Vol. 26, No. 1, 1-7